Implementing nucleus estates and smallholders system in the fisheries industry : pt ocean mitramas - Permata Kasih, Kezia; Rudy Sirait, Socrates (The Indonesian Journal of Business Administration, 2016)
Abstract -There is a significant rise in demand for global fish consumption that follows the inevitable growth of world population. Since people are more aware about nutrition, fish has become more than just a dish to appease hunger.  World per capita fish consumption has been continuously increasing from time to time , with the most growth contributed by East Asian countries such as Japan and China and Southeast Asia such as Indonesia. A larger global population and the increase in income per capita, especially in developing countries, is projected to make the biggest impact in the rise of the demand for quality foods –food with better nutrition. This will open up promising investment and business opportunities in the fisheries industry.  The importance fish supply, has taken the world’s attention that small-scale fisheries (SSF) plays a big role in satisfying that need, the welfare of the fishermen in these countries however remains neglected or has not improved significantly. PT. Ocean Mitramas is a formal entity with line of business in fish capture in Indonesia. It focuses on the business market segment (B2B). The company that has been running since 1997. To answer the growing market demands and elongate the reach of the fishermen, Ocean Mitramas plans to implement a modified Nucleus Estates and Smallholders program (Sistem Inti-Plasma). The modified Inti-Plasma system will also serve as a Corporate Social Responsibility act. The Nucleus Estate and Smallholder (NES) program was designed in the 1970s by the Indonesian government. It was initially aimed to increase the farm incomes of landless families. The intention was also to increase productivities of desired agricultural products for the purpose of exports. The scheme of the program is to include the involvement of the private sector in stimulating the economy. Proposed strategy are generated by analyzing external and internal factors that impact the company’s and fishermen’s community productivities that will then be developed into a more compact business strategy approach using TOWS matrix, market segmentation and Porters generic strategy. The solutions and the SWOT analysis of implementing the program are afterwards concluded with the implementation plan included within the achievement of intended initial proposed solution.  Keywords: Fisheries, Business Strategy, Indonesia, Nucleus Estate Smallholders